Balancing Technological Advancement and Regulatory Compliance: The Role of Administrative Coercion in Radio Frequency Spectrum Management - Silaban, M. Bakti Saleh; Ramon Nofrial; Lagat Parroha Patar Siadari; Erniyanti; Surya Respationo (Enigma in Law, 2024)
The radio frequency spectrum, an indispensable resource for wireless communication, is facing unprecedented demand due to the rapid proliferation of technologies. The efficient and compliant use of this finite resource is crucial to ensure seamless communication and prevent interference. Administrative coercion, a tool used by regulatory bodies to enforce compliance, plays a pivotal role in spectrum management. This paper explores the delicate balance between fostering technological advancement and maintaining regulatory compliance in the context of radio frequency spectrum management, with a focus on the role of administrative coercion. The research employs a mixed-method approach, combining a comprehensive literature review with empirical analysis. The literature review examines existing legal frameworks, regulatory policies, and scholarly works related to spectrum management and administrative coercion. The empirical analysis involves case studies of spectrum management practices in different regions, focusing on the application of administrative coercion. The data collected is analyzed to identify trends, challenges, and best practices in balancing technological advancement and regulatory compliance. The findings highlight the critical role of administrative coercion in ensuring the efficient and compliant use of the radio frequency spectrum. The study reveals that a well-structured and transparent administrative coercion framework can effectively deter non-compliance and promote responsible spectrum usage. However, the research also underscores the importance of striking a balance between enforcement and innovation. Overly stringent or arbitrary application of administrative coercion can stifle technological advancement and hinder the development of new wireless technologies. The study concludes that administrative coercion is an essential tool in radio frequency spectrum management, but its application requires careful consideration to balance the need for regulatory compliance with the imperative of technological advancement.